Oxidant and Antioxidant Balance in Children with Community-Acquired Pneumonia - Aykac, Kubra; Ozsurekci, Yasemin; Tanir Basaranoglu, Sevgen; Avcioglu, Gamze; Karadag Oncel, Eda; Erel, Ozcan; Cengiz, Ali Bulent; Karahan, Sevilay; Ceyhan, Mehmet (Journal of Pediatric Infectious Diseases, 2021)
Objective The balance between oxidant and antioxidant defense mechanisms is crucial. In this article, we aimed to evaluate the role of this balance in community-acquired pneumonia (CAP) in children.Methods We analyzed serum oxidant and antioxidant stress parameters according to the clinical and demographic data of children with CAP and compared them with healthy controls. Serum total antioxidant status (TAS) and total oxidant status (TOS) were evaluated and compared between the groups, along with levels of ischemia-modified albumin (IMA), antioxidant enzymes, nonenzymatic antioxidant factors, and plasma thiol.Results Of 160 children evaluated, 106 had CAP (54 outpatients and 52 inpatients), and the other 54 were healthy (control group). Total thiol and native thiol levels were significantly lower in the inpatient group compared with the outpatient group (p = 0.004 and p = 0.005, respectively). Serum IMA differed significantly among the groups (p = 0.001), with inpatients showing the highest level. A positive correlation was found between serum IMA and C-reactive protein levels in patients with pneumonia (r = 0.351; p = 0.001).Conclusion Parameters that provide information about antioxidant capacity may be useful in the diagnosis and prognosis of pneumonia. Our results suggest that plasma thiol levels and IMA may be good candidate biomarkers to predict hospitalization for CAP in children.
Keywords: oxidative stress; pneumonia; children